Upaya Pengembangan Kompetensi Guru Sekolah Dasar Dalam Kurikulum Merdeka Belajar - Gilang Kartika Hanum; Andri Cahyo Purnomo; Desy Apriani; Ita Erliyani (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2024)
The aim of the research aimed at this research is to clarify efforts to increase teacher capabilities with the title "activator school". This type of research refers to a qualitative descriptive approach carried out at one of the activator schools, namely SDN Cibaga 2, Serang district. Sampling used purposive sampling. The primary data collection carried out was obtained from observations accompanied by discussions with several teachers. Meanwhile, the selunder data uses previous references from various sources in the form of articles indexed by SINTA to internationally. In conducting interviews, it is carried out by providing a semi-structured form, after which the data results are analyzed using reduction and drawing conclusions. This research obtained results showing that activator schools strive to develop learning activities that embody the character of Pancasila for their students. One element that needs to be improved is the teacher's ability to innovate lesson plans that contain the character of Pancasila. Online training steps carried out in a short time are a concern for activator teachers, because they limit training possibilities for the development and application of indicators. Schools are encouraged to seek information from relevant educational institutions.